Dissolved oxygen concentration inversion based on Himawari-8 data and deep learning: a case study of lake Taihu - Shi, Kaifang; Lang, Qi; Wang, Peng; Yang, Wenhao; Chen, Guoxin; Yin, Hang; Zhang, Qian; Li, Wei; Wang, Haozhi (Frontiers in Environmental Science, 2023)
Dissolved Oxygen (DO) concentration is an essential water quality parameter widely used in water environments and pollution assessments, which indirectly reflects the pollution level and the occurrence of blue-green algae. With the advancement of satellite technology, the use of remote sensing techniques to estimate DO concentration has become a crucial means of water quality monitoring. In this study, we propose a novel model for DO concentration estimation in water bodies, termed Dissolved Oxygen Multimodal Deep Neural Network (DO-MDNN), which utilizes synchronous satellite remote sensing data for real-time DO concentration inversion. Using Lake Taihu as a case study, we validate the DO-MDNN model using Himawari-8 (H8) satellite imagery as input data and actual DO concentration in Lake Taihu as output data.The research results demonstrate that the DO-MDNN model exhibits high accuracy and stability in DO concentration inversion. For Lake Taihu, the performance metrics including adj_R 2 , RMSE, Pbias, and SMAPE are 0.77, 0.66 mg/L, -0.44%, and 5.36%, respectively. Compared to the average performance of other machine learning models, the adj_R 2 shows an improvement of 6.40%, RMSE is reduced by 8.27%, and SMAPE is decreased by 12.1%. These findings highlight the operational feasibility of real-time DO concentration inversion using synchronous satellite data, providing a more efficient, economical, and accurate approach for real-time DO monitoring. This method holds significant practical value in enhancing the efficiency and precision of water environment monitoring.